’We Didn’t Think It Would be Well Received’: The Gay Alliance of Students’ Legal Victory over Virginia Commonwealth University, 1974–1976 - Hevel, Michael S.; Cain, Timothy Reese (Historia y Memoria de la Educación, 2023)
In 1974, a group of college students attempted to undertake the simple act of registering an official student organization at Virginia Commonwealth University (VCU). In contrast to every other student group that had sought such status, the group, the Gay Alliance of Students (GAS), was denied registration. They were denied because the group was composed of LGBTQI+ students who wanted to promote the well-being and understanding of themselves and other LGBTQI+ individuals on campus. This article examines the founding, experience, and legal battles of GAS, an important organization in both the history of LGBTQI+ students and the history of LGBTQI+ rights more broadly. In response to its denial, GAS sued VCU in US federal district court, claiming violations of its fundamental rights under the US Constitution. After a split decision in its initial case, GAS appealed and won a resounding victory over VCU administrators and their attempts to deny LGBTQI+ students their rights. That victory was the first ever for an LGBTQI+ student organization at the federal appellate level and set a precedent for other LGBTQI+ students in five states. This article uses historical methods to situate these efforts in their institutional and local context, contribute to the nascent literature on LGBTQI+ student legal cases, and consider this key case that had implications beyond VCU and, indeed, beyond higher education.